Biology and Epidemiology of Venturia Species Affecting Fruit Crops: A Review - González-Domínguez, Elisa; Armengol, Josep; Rossi, Vittorio (Frontiers in Plant Science, 2017)
The fungal genus Venturia Sacc. (anamorph Fusicladium Bonord.) includes plant pathogens that cause substantial economic damage to fruit crops worldwide. Although Venturia inaequalis is considered a model species in plant pathology, other Venturia spp. also cause scab on other fruit trees. Relative to the substantial research that has been conducted on V. inaequalis and apple scab, little research has been conducted on Venturia spp. affecting other fruit trees. In this review, the main characteristics of plant-pathogenic species of Venturia are discussed with special attention to V. inaequalis affecting apple, V. pyrina affecting European pear, V. nashicola affecting Asian pear, V. carpophila affecting peach and almond, Fusicladium oleagineum affecting olive, F. effusum affecting pecan, and F. eriobotryae affecting loquat. This review has two main objectives: (i) to identify the main gaps in our knowledge regarding the biology and epidemiology of Venturia spp. affecting fruit trees; and (ii) to identify similarities and differences among these Venturia spp. in order to improve disease management. A thorough review has been conducted of studies regarding the phylogenetic relationships, host ranges, biologies, and epidemiologies of Venturia spp. A multiple correspondence analysis (CA) has also been performed on the main epidemiological components of these Venturia spp. CA separated the Venturia spp. into two main groups, according to their epidemiological behavior: the first group included V. inaequalis, V. pyrina, V. nashicola, and V. carpophila, the second F. oleagineum and F. eriobotryae, with F. effusum having an intermediate position. This review shows that Venturia spp. affecting fruit trees are highly host-specific, and that important gaps in understanding the life cycle exist for some species, including V. pyrina; gaps include pseudothecia formation, ascospore and conidia germination, and mycelial growth. Considering the epidemiological information reviewed, this paper shows that the use of Mills tables to predict infection periods should be avoided for Venturia spp. other than V. inaequalis.